Pelatihan Kelompok Ibu Menyusui di Desa Penyengat Olak Muaro Jambi Tahun 2019 - Yuli Suryanti; Lia Artika Sari; Ika Murtiyarini (Jurnal Abdimas Kesehatan (JAK), 2021)
Maternal and child health is one of the priority aspects to consider. Based on the results of the 2012 Indonesian Demographic and Health Survey (IDHS), it was shown that the neonates mortality rate in 2012 was 19 per 1000 live births. This problem arises in part related to the problem of breastfeeding. The results of the screening for the nutritional status of toddlers at the posyandu showed that as many as 11 toddlers were malnourished, this was due to the low knowledge of mothers regarding the balanced nutrition of toddlers, poor attitudes in fulfilling balanced nutrition for toddlers, and poor culture in fulfilling toddler nutrition. The main target of this program is assistance for the formation and training of Breastfeeding Mothers' Groups in an effort to improve the health status of mothers, babies and toddlers in Penyengat Olak Village, Kec. Jambi Outside the City. The output of this program is there is an increase in community participation in improving the health of mothers and children by assisting the formation of groups of breastfeeding mothers. The implementation of the activity was started with an observation of the breastfeeding mothers research group in several Penyengat Olak village which consisted of 3 breastfeeding mothers' groups, namely in the RT. 18, RT 19, and RT 20. Each group consists of 10 people consisting of pregnant women and nursing mothers. It is hoped that the continuity of breastfeeding mother's breastfeeding program can be maintained, even though there are many factors raised by members, such as being busy taking care of the house and children, inappropriate meeting times, long distances, and so on.